You know that -3 is the Y intercept(vertical graph line) and then continue 2/1 every x value that is plugged in.
The answer is: y= 2/3x +5
Answer:
(a-b) *(a-b) *(a-b)
=(a*a*a) -3*(a*a*b)+3*(a*b*b)-(b*b*b)
34000*(1-7%)*(1-7%)*(1-7%)
=34000*(1-0.07)*(1-0.07)*(1-0.07)
=34000*[(1*1*1)-3*(1*1*0.07)+3*(1*0.07*0.07)-(0.07*0.07*0.07)]
=34000*(1-0.21+0.0147-0.000343)
=34000*(0.804357)
=34*1000*(804.357/1000)
=34*804.357
=<u>27348.138</u>
<u>=</u><u>27348</u>
Answer:
![f(10) = 35 \\ \\ f( - 11) = 39 \\ \\ f(12) = 53 \\ \\ f(2) = 13](https://tex.z-dn.net/?f=f%2810%29%20%3D%2035%20%5C%5C%20%20%5C%5C%20f%28%20-%2011%29%20%3D%2039%20%5C%5C%20%20%5C%5C%20f%2812%29%20%3D%2053%20%5C%5C%20%20%5C%5C%20f%282%29%20%3D%2013)
Step-by-step explanation:
![f(x) = | - 5 - 4x|](https://tex.z-dn.net/?f=%20f%28x%29%20%20%3D%20%20%7C%20-%205%20-%204x%7C%20)
To solve for the following substitute the value of x in the brackets into the above formula and solve for the value of x
<u>NB</u><u>:</u><u> </u> Absolute value of a negative number is the same number but positive.
So we have
![f( - 10) = | - 5 - 4( - 10)| \\ = | - 5 + 40| = 35 \\ \\ f( - 11) = | - 5 - 4( - 11)| \\ = | - 5 + 44| = 39 \\ \\ f(12) = | - 5 - 4(12)| \\ = | - 5 - 48| \\ = | - 53| = 53 \\ \\ f(2) = | - 5 - 4(2)| \\ = | - 5 - 8| = | - 13| \\ = 13](https://tex.z-dn.net/?f=f%28%20-%2010%29%20%3D%20%20%7C%20-%205%20-%204%28%20-%2010%29%7C%20%20%5C%5C%20%20%3D%20%20%7C%20-%205%20%2B%2040%7C%20%20%3D%2035%20%5C%5C%20%20%5C%5C%20f%28%20-%2011%29%20%3D%20%20%7C%20-%205%20-%204%28%20-%2011%29%7C%20%20%5C%5C%20%20%3D%20%20%7C%20-%205%20%2B%2044%7C%20%20%3D%2039%20%5C%5C%20%20%5C%5C%20f%2812%29%20%3D%20%20%7C%20-%205%20-%204%2812%29%7C%20%20%5C%5C%20%20%3D%20%20%7C%20-%205%20-%2048%7C%20%20%20%5C%5C%20%20%3D%20%20%7C%20-%2053%7C%20%20%3D%2053%20%5C%5C%20%20%5C%5C%20f%282%29%20%3D%20%20%7C%20-%205%20-%204%282%29%7C%20%20%5C%5C%20%20%3D%20%20%7C%20-%205%20-%208%7C%20%20%3D%20%20%7C%20-%2013%7C%20%20%5C%5C%20%20%3D%2013)
Hope this helps you
I'm not quite sure these are right. You might wanna check with a classmate or something first.
Step-by-step explanation:
(6x + 10) + (x + 17) + (4x - 34) = 180
11x - 7 = 180
11x = 173
x = 15.73 (answer had repeating decimal so i rounded up in the hundredths place)
(6x + 10)
6 (15.73) + 10
94.38 + 10
104.38
(x + 17)
(15.73) + 17
32.73
(4x - 34)
4(15.73) - 34
62.92 - 34
28.92